PENDAMPINGAN BUDIDAYA AYAM KUB PADA KELOMPOK WANITA TANI (KWT) NISKALA BANTUL DAERAH ISTIMEWA YOGYAKARTA - Irawati, Hani; Okimustava, Okimustava; Arief Ghozali, Fanani (Universitas Mataram, 2024)
Community service is one part of the tridharma of higher education that must be carried out by lecturers. Community service provides space for lecturers to apply their knowledge in the community. One of the community service activities carried out by Ahmad Dahlan University lecturers is by holding training and mentoring KUB chicken cultivation at the Niskala Bantul DIY Farmer Women Group (KWT). The purpose of this service activity is to provide knowledge and assistance to KWT Niskala about KUB chicken cultivation. The initial knowledge of the trainees was measured using pretest questions and after the training activities, a test post was carried out to determine the improvement of the trainees' understanding. Based on the results of the postes, it is known that there is an increase in knowledge related to KUB chicken cultivation, in addition to that based on the assistance carried out, a good increase in the weight of KUB chickens is obtained.